2020
DOI: 10.1093/ejo/cjaa027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of facemask in patients with unilateral cleft lip and palate: a systematic review and meta-analysis

Abstract: Summary Background Patients with cleft lip and palate usually present a Class III skeletal pattern. Facemask (FM) is one of the conventional orthodontic treatment modalities used to address the skeletal discrepancy in cleft patients. Objective To investigate the potential effectiveness of FM in unilateral cleft lip and palate (UCLP) patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…Compared with Palikaraki et al's study, 20 the current systematic review, which investigated the effects of BAMP treatment on all developing patients with unilateral and bilateral cleft lip and palate in the related articles, indicated that the SNA and ANB exclusively showed a significant positive difference in support of treatment, and SNB and SN-MP indicated only marginally different values.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Compared with Palikaraki et al's study, 20 the current systematic review, which investigated the effects of BAMP treatment on all developing patients with unilateral and bilateral cleft lip and palate in the related articles, indicated that the SNA and ANB exclusively showed a significant positive difference in support of treatment, and SNB and SN-MP indicated only marginally different values.…”
Section: Discussioncontrasting
confidence: 79%
“…In the systematic review and meta-analysis of Palikaraki et al's study in 2021, 20 the effects of the tooth-born facemask on patients with unilateral cleft lip/palate was examined. A statistically significant difference was established in the values of the landmarks SNA, SNB, ANB, and SN-MP between before and after the treatment phases.…”
Section: Discussionmentioning
confidence: 99%
“…Palikaraki et al reports similar skeletal responses to PHG among patients with UCLP with or without expansion and showed approximately 2° improvements in SNA and SNB, 4° change in ANB, and 2° increase in MPA. 28 These changes are in concordance with short-term effects of PHG in young patients without CLP. 16 Proclination of the upper incisors is also significant post-PHG in both our sample and in the literature for patients with and without CLP.…”
Section: Resultssupporting
confidence: 72%
“…In this review, skeletal Class III relationship was effectively corrected by the advancement of A point regardless of the MAMP type (range of ΔSNA, 0.5°-4.2° in type 1; 1.2°-1.7° in type 2; range of ΔANB, 0.6°-3.0° in type 1, and 1.0°-3.5° in type 2; Table 1), which was similar to the results from a recent meta-analysis of MAMP in non-cleft patients 24 and conventional facemask treatment in cleft patients. 25 Therefore, it can be stated that the sagittal skeletal discrepancy in the maxillomandibular complex was corrected primarily by maxillary advancement rather than mandibular repositioning in MAMP therapy.…”
Section: Considerations Of the Skeletal Changes By Mamp Therapymentioning
confidence: 99%